Obstetric and Neonatal Complications in Pregnancies Conceived after Oocyte Donation: A Systematic Review and Meta-Analysis. Issue 4 (December 2017) - Storgaard, M.; Loft, A.; Bergh, C.; Wennerholm, U.B.; Soderstrom-Anttila, V.; Romundstad, L.B.; Aittomaki, K.; Oldereid, N.; Forman, J.; Pinborg, A.
Abstract : ( BJOG 2017;124:561–572) There are over 50, 000 oocyte donation (OD) treatments performed annually in the United State and Europe. OD pregnancies have been linked with increased risks of preeclampsia, low birth weight, preterm birth, and cesarean section. This systematic review and meta-analysis was performed to determine if OD pregnancies are associated with higher incidences of adverse pregnancy outcomes. Obstetric complications and neonatal outcomes were compared between OD pregnancies and pregnancies conceived by other methods, including autologous in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI), and spontaneous conception (SC).